2011
DOI: 10.1016/j.egypro.2011.02.286
|View full text |Cite
|
Sign up to set email alerts
|

In Salah CO2 injection modeling: A preliminary approach to predict short term reservoir behavior

Abstract: International audienceA short term performance assessment methodology under development and validation at the In Salah CO2 storage site is presented. The progressive approach first concludes of the necessity to consider a dual media reservoir system at Krechba to fit with gas reservoir production, CO2 injection and CO2 breakthrough at an old appraisal well (Kb-5). To improve gas migration prediction while also considering the geomechanical behavior of the site, an extended geomodel has been developed. Fluid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…[], Preisig and Prévost [], and Deflandre et al . [], compared to the critical point of CO 2 at 31°C and 7.4 MPa [ Lide , ]). Second, mutual dissolution of the phases is ignored.…”
Section: Governing Equationsmentioning
confidence: 99%
“…[], Preisig and Prévost [], and Deflandre et al . [], compared to the critical point of CO 2 at 31°C and 7.4 MPa [ Lide , ]). Second, mutual dissolution of the phases is ignored.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Also worth noting here is the fact that previous work on model calibration has utilized both manual and automated calibration approaches. In manual calibration, parameters affecting the performance metrics of interest are adjusted by the modeler until a satisfactory ‘match’ is obtained.…”
Section: Model Calibration Strategymentioning
confidence: 99%
“…Delfandre et al used a dual media model to history match pressure evolution and observed CO 2 breakthrough at an old appraisal well located close to one of the CO 2 injection wells in the Krebcha field of the In Salah Gas Project in Algeria. They used a fracture network characterized by long fractures and faults spaced 1000–2000 m apart in order to match pressure response and breakthrough times.…”
Section: Introduction and Scopementioning
confidence: 99%
“…This paper presents the main features of the geological model of the storage complex with its stratigraphic and petrophysical properties. The characterization workflow applied to fractured sandstone formations at In-Salah [8] is transposed to naturally fractured carbonate. These reservoirs are particularly challenging to handle because of their high level of heterogeneity that conditions the reservoir behaviour during the injection.…”
Section: Introductionmentioning
confidence: 99%